2021
DOI: 10.31234/osf.io/scnke
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Acoustic Features and Didactic Function of Foreigner Directed Speech: A literature Review.

Abstract: This review considers the acoustic features of a clear speech register directed to non-native listeners known as Foreigner Directed Speech (FDS). We identify vowel hyperarticulation and low speech rate as the most representative acoustic features of FDS; other features, including wide pitch range and high intensity, are still under debate.We also discuss factors that may influence the outcomes and characteristics of FDS. We start by examining accommodation theories (Lindblom, 1990), outlining the reasons why F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 120 publications
1
2
0
Order By: Relevance
“…An important consideration is that the present study used an online method to collect participants' responses. Several studies have addressed the question of whether online experiments provide reliable results and revealed that chronometric experiments for speech production can be implemented online without information loss (Anwyl-Irvine et al, 2020; Bridges et al, 2020;Fairs & Strijkers, 2021;Piazza, Kartushina, et al, 2022;Vogt et al, 2021). Thus, we are con dent in sustaining that the differences we found between speech register groups were genuine and not driven by the online setting.…”
Section: Theories Of Second Language Acquisition That Explain the Nnd...supporting
confidence: 61%
“…An important consideration is that the present study used an online method to collect participants' responses. Several studies have addressed the question of whether online experiments provide reliable results and revealed that chronometric experiments for speech production can be implemented online without information loss (Anwyl-Irvine et al, 2020; Bridges et al, 2020;Fairs & Strijkers, 2021;Piazza, Kartushina, et al, 2022;Vogt et al, 2021). Thus, we are con dent in sustaining that the differences we found between speech register groups were genuine and not driven by the online setting.…”
Section: Theories Of Second Language Acquisition That Explain the Nnd...supporting
confidence: 61%
“…Although the appropriate spoken word identification and therefore speech intelligibility had previously been found to be affected by how accurate vowels are articulated (Liu et al, 2005;Weismer et al, 2001), other acoustic-phonetic features have also been highlighted in clear speech perception such as increased vowel length and word length (Bond and Moore, 1994;Scarborough et al, 2007). For example, increased word length was observed to be part of clear speech (Bond and Moore, 1994;Piazza et al, 2021) and increased vowel length was reported in speech to foreigners (Ashby, 2004;Sankowska et al, 2011). It could therefore be stated that it is a combination of vowel space together with other acoustic-phonetic features that might contribute to clear speech.…”
Section: Discussionmentioning
confidence: 98%
“…An important consideration is that the present study used an online method to collect participants' responses. Several studies have addressed the question of whether online experiments provide reliable results and revealed that chronometric experiments for speech production can be implemented online without information loss [74][75][76][77][78] . Thus, we are confident in sustaining that the differences we found between speech register groups were genuine and not driven by the online setting.…”
Section: Nnds Benefit Depends On the Modality And Task Demandsmentioning
confidence: 99%